(untitled) (Gestionar: revista de empresa y gobierno, 2021)
This research arises from the limited participation of the community in the Local Health Administration Council (CLAS) with activities of an operational nature (campaigns, talks, etc.) focused only on the administration of services, with little concern for quality. Of life, the determinants of the population’s health, and the fulfillment of citizens’ rights in health; for which there is an absence of channels in Co-management and citizen participation. The research was of a descriptive type with a comparative design; the population was made up of the inhabitants of the districts of Atuncolla and Chancachi, with a sample of 338 and 291, respectively, whose unit of analysis was constituted by the head of the family by estimating a population proportion. The information was obtained through the questionnaire regarding knowledge (established on the Likert scale). The data was processed through the statistical analysis of Chi-Square. The results determine that the level of perception that the population has about the state policy about the CLAS is made up of poor knowledge. In the CLAS Chancachi, the inhabitants do not know the meaning of CLAS, the bodies that comprise it, the members of the Board of Directors, as well as the functions they perform, the person in charge who manages the budget, and the requirements to be elected representative of the general assembly. In the CLAS Atuncolla, they do not know which bodies make up the CLAS who are responsible for managing the budget, participating in the hiring of personnel, and renewal time of the members of the General Assembly. Most of the inhabitants show indifferent attitudes with a tendency to be negative; meanwhile, in the CLAS Atuncolla, the tendency is to be positive; those that will incur negatively in Co-management and citizen participation. Both beneficiary populations show high expectations regarding the organization and functioning of the CLAS, which will allow the improvement and reformulation of the State Health Policy.